Tackling the effects of atmospheric dust hazard on human health - Emmanouil Proestakis (Field Actions Science Reports)
What is the contribution of the inhalable component of atmospheric dust to the total aerosol load? How much of it resides close to the Earth’s surface, where most human activity takes place? To what extent has it changed over the highly-industrialized and densely-populated areas/Megacities over the last two decades and over which areas is the atmospheric concentration foreseen to exceed the World Health Organization Air Quality Guidelines in the near-future? To what extent have dust emissions changed since the pre-industrial times and what can the national and international initiatives say about the amount of dust that will reside in the atmosphere by the end of the century? The article discusses the current status of pressing societal questions related to the health risk posed by the inhalable component of atmospheric dust, which are made even more pressing by the ongoing climate change. Insights are delivered under the prism of ongoing international initiatives, recent advancements, and the challenging limitations of our capabilities.